Successional Herbaceous Species Affect Soil Processes in a High-Elevation Alpine Proglacial Chronosequence - Mainetti, Andrea; D’Amico, Michele; Probo, Massimiliano; Quaglia, Elena; Ravetto Enri, Simone; Celi, Luisella; Lonati, Michele (Frontiers in Environmental Science, 2021)
The study investigated plant-soil interactions along a proglacial chronosequence in the Italian Alps, with a specific focus on pioneer and grassland species structure and biogeochemical processes, with the aim to evaluate the biotic patterns in ecosystem development. We recorded vascular plant frequencies and the mean diameter of one pioneer and one grassland target species in 18 permanent plots distributed along six different stages encompassing a 170-years chronosequence in the Lauson Glacier forefield (NW Italy). We evaluated the main soil properties and measured the C:N:P stoichiometry in the biomass of pioneer and grassland target species and in the underlying soil. For comparative purposes, we analyzed also bare soils sampled near the sampled plant individuals. Pioneer species number and cover significantly increased 10 and 40 years after deglaciation respectively, while alpine grassland species cover and number peaked only after 65 and 140 years, respectively. Along the chronosequence, soils beneath vascular plants were enriched in nutrients, especially under individuals of alpine grassland species, with total organic C contents ranging between 1.3 and 8.9 g·kg−1 compared to 0.2 and 3.3 g·kg−1 in bare soils. Nitrogen content in bare soils was nearly undetectable, while it increased in the plant-affected soils, leading to a more balanced C:N:P stoichiometry in the oldest stages. The colonization of alpine grassland species started immediately, although species number and cover increased only when the soil acquired sufficient nutrient supply and functionality. Although the ecosystem remained C and N limited, the soil could provide adequate conditions for more competitive species establishment, as confirmed by the increasing number and cover of alpine grassland species. Thus, soil nutrient dynamics were strongly influenced by plants, with a major influence triggered by late-successional grassland species.